A Compact Antenna Design for Fifth Generation Wireless Communication System - N. N., Mohd Daud; Mohamed Nasrun, Osman; Muhammad Ramlee, Kamarudin; Abdul Rahman, Kram; Muhammad Mokhzaini, Azizan (EDP Sciences, 2017)
This paper proposes a compact antenna design for wireless communication system that can operate at dual band frequencies which are 24.25 GHz and 38 GHz. The antenna with an overall size of 6.3 mm X 6.0 mm is printed on RogersRT5880 type of substrate with a thickness of 0.787 mm. The simulated reflection coefficient result is < -10 dB for both frequencies which makes it suitable for 5G applications. The proposed antenna has a stable gain value of 7.23 dBi at 24.25 GHz and 3.69 dBi at 38 GHz. All the simulation result was performed by using CST Microwave Studio Software. The result shows the feasibility of this antenna to be applied for future 5G application. © The Authors, published by EDP Sciences, 2017.